Companionship during childbirth: As experienced and perceived in rural Nepal, Sindhupalchowk - Joshi, Rujina; Naravage, Wanapa (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To explore the experiences and the perceptions of reproductive-aged women and their main influencers, including husbands or mothers-in-law during their most recent institutional delivery regarding companionship during childbirth. To identify the experiences and perceptions of nursing staff regarding companionship during childbirth. Methods: A qualitative approach was adopted to interview chosen eleven reproductive-aged women, five main influencers (three husbands and two mothers-in-law) and three nursing staff of Melamchi Primary Health Care Center by purposive sampling, in a community setting. Results: Overall, almost all the women were not allowed to be accompanied by their relatives during childbirth in the Primary Health Care Center, when majority of them wanted company of their husbands, followed by female relatives. The nursing staff also concurred to the need of companionship during childbirth for support. On the contrary, a few interviewed women and all the husbands did not find any importance of companionship to the women in labor. Main reasons expressed were the ignorance among husbands to support their partners during childbirth and a feeling of shyness or discomfort among women in presence of known person during the process. Conclusion: The practice regarding the provision of companionship during childbirth is not congruent to the felt need for and importance of it by majority of women and nursing staff. Privacy, infection control and institutional policy were the concern for companionship during childbirth. Key words: childbirth, companionship, experience, perception, Respectful Maternity Care